(untitled) (Philosophy and Progress, 2014)
The aim of this paper is to explore the basic trend of Indian thoughts from early date to the present day. This can never be denied that it is dialectics or contradictory approach which might be thought to be the basic tenet of its socio- scientific ameliorations. Dialectics, here, is taken to be synonymous with contradictions or debate. Accordingly, the intention is to show the major contending passions of this land and their reconciliations thereby which become the most pivotal issue for Indian argumentations. DOI: http://dx.doi.org/10.3329/pp.v51i1-2.17679